2014
DOI: 10.1002/mrm.25456
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study to simulate the intracardiac magnetohydrodynamic effect

Abstract: The in vitro model allows investigation of MHD effects on intracardiac electrograms. A phase contrast MR scan was successfully applied to characterize and estimate the MHD distortion on intracardiac signals allowing correction of these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…32,33 Of greater practical concern is that positive and negative ions in blood are pushed in opposite directions by the Lorentz force, causing a charge separation and an electric field that corrupts electrocardiograms and complicates the task of performing cardiac-gated MRI. [35][36][37] It is well known that movement in a magnetic field can induce a voltage (due to Faraday's law of induction, discussed in more detail later) in electrically conductive materials, including biological tissues, especially when the motion is through regions of space where the magnetic field changes steeply. For example, near the entry to the bore of a 3T MRI where j$B o j tends to be greatest, it can be shown that current densities over 0.1 A/m 2 may be produced in conductive tissues due to the voltage induced by normal movement.…”
Section: Direct Interactions Between the Static Magnetic Field And LImentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Of greater practical concern is that positive and negative ions in blood are pushed in opposite directions by the Lorentz force, causing a charge separation and an electric field that corrupts electrocardiograms and complicates the task of performing cardiac-gated MRI. [35][36][37] It is well known that movement in a magnetic field can induce a voltage (due to Faraday's law of induction, discussed in more detail later) in electrically conductive materials, including biological tissues, especially when the motion is through regions of space where the magnetic field changes steeply. For example, near the entry to the bore of a 3T MRI where j$B o j tends to be greatest, it can be shown that current densities over 0.1 A/m 2 may be produced in conductive tissues due to the voltage induced by normal movement.…”
Section: Direct Interactions Between the Static Magnetic Field And LImentioning
confidence: 99%
“…Blood flowing in a direction orthogonal to a magnetic field experiences a reverse pressure impeding the flow, but this is expected to result in an insignificant increase in blood pressure even in a high‐field MRI . Of greater practical concern is that positive and negative ions in blood are pushed in opposite directions by the Lorentz force, causing a charge separation and an electric field that corrupts electrocardiograms and complicates the task of performing cardiac‐gated MRI …”
Section: The Static Magnetic Fieldmentioning
confidence: 99%
“…[ 74,79 ] Similarly, a phantom in vitro model was developed to record bipolar VMHD signals ( Figure 4 a) and shown to be comparable to a simplifi ed analytical model in an MRI environment (Figure 4 b), predicting a linear dependence on fi eld strength. [ 80 ] The phantom model was constructed using rigid plastic tubing, a fl uid reservoir, and a ventricular assist device, allowing the device to circulate a volume of conducting fl uid while maintaining MRI-compatibility.…”
Section: Other Microscale Mhd Devices and Applicationsmentioning
confidence: 99%
“…Using a flow phantom placed inside an MRI, as well as a pump which provided pulsatile flow, V MHD was reproduced in vitro. In addition, the correlation between V MHD observed on conventional ECG traces and cardiac blood flow was demonstrated [19]. Current modeling approaches have been able to successfully simulate the induced V MHD as a linear combination of the true ECG signal and a V MHD term (Eq 1) with an additional scaling factor which was dependent on the measurement electrode selected [20].…”
Section: Introductionmentioning
confidence: 99%